Blockchain Governance Challenges: Beyond Libertarianism - Korhonen Outi; Rantala Juho (Cambridge University Press, 2022)
This essay considers the ideological context of blockchain technology. This technology is often celebrated for its potential for decentralization, distribution, privacy, and a lack of intermediaries and coordinators for transactions and general governance. Because of these features, blockchain technology, and, in particular, its most famous inauguration—the bitcoin blockchain—is frequently identified with libertarianism. In this essay, we argue that the ideological context of blockchain technology is much more complicated. In addition to unraveling a number of background ideologies and their role in this technology, we raise the ontological issue concerning the relationship of ideology to technology. These matters have implications for, among other things, the approach that should be taken to blockchain's governance, as well as how international lawyers may approach this “foreign”-seeming phenomenon that has its proponents from the European Central Bank to the United Nations (not, however, forgetting the private sector nor the digital underground).